Analisis Pengaruh Pertumbuhan Ekonomi, Tingkat Pendidikan, dan Tingkat Kemiskinan Terhadap Indeks Pembangunan Manusia (IPM) di Indonesia Tahun 2019–2023 - Febri Stiawan; Tuty Sariwulan; Siti Nurjannah (Jurnal Ilmiah Ekonomi dan Manajemen Indonesia, 2026)
This study aims to analyze the effect of economic growth, education level, and poverty rate on the Human Development Index (HDI) in Indonesia during the period of 2019–2023. The study was motivated by disparities in human development across provinces in Indonesia despite the overall upward trend in the national HDI. In addition, fluctuations in economic growth due to the COVID-19 pandemic, improvements in educational attainment, and changes in poverty levels are presumed to influence the quality of human development in Indonesia. This study employed a quantitative approach using secondary panel data covering 34 provinces in Indonesia from 2019 to 2023. The data were obtained from Statistics Indonesia (Badan Pusat Statistik/BPS). The data were analyzed using panel data regression, including model selection through the Chow Test, Hausman Test, and Lagrange Multiplier Test, followed by classical assumption tests, partial significance tests (t-test), simultaneous significance tests (F-test), and the coefficient of determination (Adjusted R²). The results indicate that, partially, economic growth has a positive effect on the Human Development Index (HDI), education level has a positive effect on the Human Development Index (HDI), while the poverty rate has a negative effect on the Human Development Index (HDI). Simultaneously, economic growth, education level, and poverty rate have a significant effect on the Human Development Index (HDI) in Indonesia during the 2019–2023 period. The Adjusted R² value indicates that the independent variables explain most of the variation in the Human Development Index (HDI), while the remaining variation is explained by other variables outside the research model. These findings imply that improving educational quality, promoting inclusive economic growth, and reducing poverty are essential factors in enhancing human development in Indonesia. Therefore, the government is expected to strengthen policies aimed at improving the quality of human resources, ensuring more inclusive economic growth, and accelerating poverty reduction to achieve sustainable improvements in the Human Development Index.